(untitled) (Journal of the College of Basic Education, 2025)
The distinction and success of a diplomat in the tasks assigned to them positively reflect on their country’s relations with other nations they represent. This is especially true if the diplomat possesses qualities that set them apart from their peers among ambassadors and diplomats. This was exemplified by the Moroccan diplomat Abdelhadi Tazi, who played a role in building strong relations for Morocco within its Arab and Islamic surroundings. He was assigned, for a second time, to serve as ambassador to Iraq after significant political developments in that Arab country. During his ambassadorship in Iraq, Tazi was also entrusted with additional diplomatic tasks in the Arab East, including in Abu Dhabi and Jordan, allowing him to keep his country closely informed about the nature of conflicts and political developments in the Arab and Islamic East despite the geographical distance. Tazi was also at the service of the higher authorities in Morocco for an urgent diplomatic mission in Iran, in addition to various cultural and intellectual tasks he successfully carried out. He managed to combine his diplomatic and intellectual pursuits, making each serve the other, as will be discussed in the section “Abdelhadi Tazi as a Historian and Diplomat, 1969–2014.” Despite his extensive diplomatic duties, Tazi remained true to his intellectual and cultural inclinations as a writer, historian, and researcher. He found himself deeply engaged in research and documentation for many years, which led to a body of intellectual work encompassing dozens of books he authored and edited, along with hundreds of historical research papers and studies. His contributions enriched the Arab and human library with uncovered historical heritage, documents, and sources that had been buried in the depths of libraries and documentation centers worldwide, thus placing Tazi’s intellectual legacy in the service of Arab and human heritage.